Особливості ціннісно-орієнтаційних факторів особистісного та професійного становлення майбутніх правоохоронців - Мілорадова, Н. Е.; Miloradovа, N. E.; Доценко, В. В.; Dotsenko, V. V.; Natalia Miloradova; Вікторія Доценко (Право і безпека. – 2016. – № 3 (62). – С. 12-17, 2016)
Розглянуто особливості ціннісних орієнтацій як складових фундаменту особистісного та професійного становлення правоохоронців на етапі фахової підготовки. На прикладі курсантів першого року навчання виокремлено, проаналізовано та надано змістовну інтерпретацію шістьом ціннісно-орієнтаційним факторам, що впливають на процес особистісного та професійного становлення майбутніх правоохоронців, до них віднесені: життєва активність; самовираження – емоційність у стосунках; самоконтроль – амбіційність; професійна активність – життєва ефективність; цілеспрямованість – саморозвиток; особистісна оригінальність – суспільне визнання.

The authors underline that the main constructions of the set of life values of a personality are put in a childhood. Such values are formed and developed during the process of education in the higher educational establishment. Hence, the research is needed to define the ways of professional shaping of the law enforcement officer. The article’s analysis shows that the personality value-set question has been in the scope of many scientific philosophy, sociology and psychology schools. The authors considered the following points: the set of life values of a personality features during the professional development; the first-year-related set of values was identified; their meaning in the professional development was determined. The authors identified and interpreted six value set factors, which influence the personal and professional development of the future law enforcement officers: life activity, self-actualization – emotionality, self-control – ambitiousness, professional activity – life efficiency, goal-oriented mind – selfdevelopment; personal ingenuity – public recognition. The authors underline that the above mentioned factors define the features of the personal and professional development of the future law enforcement officers during the first educational year.

Рассмотрены особенности ценностных ориентаций как составляющих фундамента личностного и профессионального становления правоохранителей на этапе профессиональной подготовки. На примере курсантов первого года обучения выделено, проанализировано и дано содержательную интерпретацию шести ценностно-ориентационным факторам, влияющим на процесс личностного и профессионального становления будущих правоохранителей, к ним отнесены: жизненная активность, самовыражение – эмоциональность в отношениях; самоконтроль – амбициозность; профессиональная активность – жизненная эффективность; целеустремленность – саморазвитие; личностная оригинальность – общественное признание.
Specific features of the personal and professional development of future law enforcement officers
Особенности ценностноориентационных факторов личностного и профессионального становления будущих правоохранителей
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; ціннісні орієнтації; ціннісно-орієнтаційні фактори; особистісне становлення; професійне становлення; майбутні правоохоронці; правоохоронці; value orientation; personal development; professional development; future law enforcement officers; law enforcement officers; ценностные ориентации; ценностно-ориентационные факторы; личностное становление; профессиональное становление; будущие правоохранители; правоохранители